PP.04 Antenatal Corticosteroids, for Women with Diabetes, Undergoing Elective Lower Uterine Segment Caesarean Section Between 38 + 0–38 + 6, are they worth it?. (26th April 2013) - Hodson, K; Lyon-Dean, C; Marshall, S; MacDougall, M
Abstract : Background: The Royal College of Obstetricians and Gynaecologists (RCOG) recently recommended antenatal corticosteroids for all women undergoing elective lower uterine segment caesarean section (El-LSCS) prior to 38 +6 weeks. National Institute for Health and Clinical Excellence recommend delivery for women with diabetes at 38 +0 weeks. Corticosteroids can destabilise maternal glycaemic control. The purpose of this study was to assess the outcomes in women with diabetes undergoing El-LSCS between 37 +6 and 38 +6 weeks who did not receive antenatal corticosteroids prior to the RCOG guideline. Methods: We performed a retrospective audit of 27, 869 consecutive live births in a tertiary referral hospital. We calculated admission rates to Special Care Baby Unit (SCBU) in those undergoing El-LSCS without corticosteroids, identifying presence of diabetes, type of diabetes and gestation at delivery. Results: 32% (n = 985/3016) of El-LSCS were performed prior to 38+6 weeks in the general population. In the diabetic population 70% (n = 51/72)of El-LSCS were performed prior to 38+6 weeks. 41.6% (n = 30/72)of which were performed between 38+0–38+6 weeks. The admission rate to SCBU in the diabetic population undergoing El-LSCS was 1.38%, lower than both the 4.7% rate in the general population undergoing El-LSCS and the 2.7% overall rate in the diabetic population. No women with diabetes undergoing El.LSCS after 37 +6 weeks had a baby admitted to SCBU despite not receiving corticosteroids. Conclusion: The admission rates to SCBU observed in babies born to mums with diabetes delivering between 38+0–38+6 by El-LSCS without corticosteroid cover, does not support their routine administration in this population, especially given the destabilising effect they have on glycaemic control.